Remembering the atomic bombing of Hiroshima and Nagasaki: Collective memory of post-war Japan - Okuda, Hiroko (Acta Orientalia Vilnensia, 2011)
Nanzan University This study examines the way in which Tokyo has exploited the atomic bombing of Hiroshima and Nagasaki as a symbolic means of inducing post-war Japanese collective identity. To consider an effort on Tokyo’s part to integrate A-bomb memories into the country’s victim consciousness rather than to overcome the past, the study compares the A-bombed cities written with different Japanese forms, the peace parks, and the peace memorials. It also analyses the news coverage by two national daily papers on the A-bomb memorial days. By doing so, the study shows how the nation has been guided in its memory by the government.